The effects of exercise on neuromuscular function in people with chronic neck pain: A systematic review and meta-analysis. - Angelo Marco Dirito; Deepa Abichandani; Ferozkhan Jadhakhan; Deborah Falla (PLoS ONE)
Background Differences in cervical neuromuscular function are commonly observed between people with and without chronic neck pain. Exercise may improve cervical neuromuscular function of people with neck pain although the evidence for this has not been systematically reviewed. Objective To systematically review the existing evidence on the effect of exercises targeting the neck muscles on neuromuscular function in people with chronic non-specific neck pain. Methods This systematic review was conducted based on a registered protocol (CRD42021298831) with searches conducted on the following databases from inception to 21st October 2023: MEDLINE, CINAHL, Web of Science, Scopus, AMED, Google Scholar, Open Grey and Zetoc. Studies of interest were trials investigating neuromuscular adaptations to a program of exercise targeting the neck muscles (>2 weeks) in people with chronic non-specific neck pain. Two reviewers independently screened the studies and performed data extraction, risk of bias assessment, and rated the overall certainty of the evidence (GRADE). Results Fourteen articles from 2110 citations were included. There is moderate certainty of evidence that the use of craniocervical flexion training (either in isolation or in combination with resistance training) can induce neural adaptations within the neck muscles. A meta-analysis showed a reduction in sternocleidomastoid muscle activity after neck exercise interventions compared to control interventions. Conclusion The articles included in this systematic review confirmed that exercise can result in neuromuscular adaptations within neck muscles, as measured by electromyography. Specificity of training was seen to be relevant for the type of neuromuscular adaptations induced.